2021
DOI: 10.1186/s41205-021-00121-9
|View full text |Cite
|
Sign up to set email alerts
|

3D printed composite model of pelvic osteochondroma and nerve roots

Abstract: Background 3D-printing has become increasingly utilized in the preoperative planning of clinical orthopaedics. Surgical treatment of bone tumours within the pelvis is challenging due to the complex 3D bone structure geometry, as well as the proximity of vital structures. We present a unique case where a composite bone and nerve model of the lower lumbar spine, pelvis and accompanying nerve roots was created using 3D-printing. The 3D-printed model created an accurate reconstruction of the pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Fox and Kanawati29 also created a 3D-printed spine model to facilitate surgical planning before tumor surgery and showed that it could enhance precision and safety (Figure 2). Although preoperative planning with RP may appear to entail greater financial burden, the subsequent likelihood of increased patient-specific anatomical knowledge, decreased operative time and blood loss, improved screw insertion accuracy, and recognition of aberrant anatomy not discernible on 2D imaging likely outweigh initial costs, providing strong evidence in favor of its use in spinal surgery 1,2,27,28,30.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…Fox and Kanawati29 also created a 3D-printed spine model to facilitate surgical planning before tumor surgery and showed that it could enhance precision and safety (Figure 2). Although preoperative planning with RP may appear to entail greater financial burden, the subsequent likelihood of increased patient-specific anatomical knowledge, decreased operative time and blood loss, improved screw insertion accuracy, and recognition of aberrant anatomy not discernible on 2D imaging likely outweigh initial costs, providing strong evidence in favor of its use in spinal surgery 1,2,27,28,30.…”
Section: Preoperative Planningmentioning
confidence: 99%